L'epistolario del Bibbiena. Appunti sul censimento delle carte autografe a mezzo secolo dall'edizione Moncallero (Quaderni di Gargnano, 2018)
The paper examines Bernardo Dovizi da Bibbiena correspondence before and after his elevation to cardinal under Pope Leo X. Starting from a new census of Bibbiena’s autograph letters, the study proposes a radical revision of the critical edition of Moncallero (published in two volumes between 1955 and 1965) with a view to completing the recension and adding to the exegetical apparatus. The paper explores the literary references, especially to the novelistic and dramatic traditions, in Bibbiena’s correspondence, along with the various jokes and humorous monikers that play on the author’s moral and physical weakness, and considers how they correspond to the character portrayed in Castiglione’s Cortegiano, in which Bibbiena is credited with making a perspicacious commentary on the rhetoric of facezia. The last part of the paper submits a group of unedited letters to historical analysis. The appendix includes a list of Bibbiena’s letters that are stored in the Medici Archive (Mediceo del Principato [MAP]) but were not included in Moncallero’s edition.
Keywords: Diplomatic correspondence; Epistolography as a literary genre; Recensio; Critical edition; Medicean papacies